High‐Resolution P‐T‐Time Paths Across Himalayan Faults Exposed Along the Bhagirathi Transect NW India: Implications for the Construction of the Himalayan Orogen and Ongoing Deformation. (21st December 2020) - Catlos, Elizabeth J.; Perez, Theresa J.; Lovera, Oscar M.; Dubey, Chandra Shekhar; Schmitt, Axel K.; Etzel, Thomas M.
Abstract: Pressure‐temperature (P‐T) conditions and high‐resolution paths from 11 garnet‐bearing rocks collected across Himalayan fault systems exposed along the Bhagirathi River (Uttarakhand, NW India) reveal the tectonic conditions responsible for their growth. A garnet from the Tethyan metasedimentary unit has a 50.3 ± 0.6 Ma (Th‐Pb, ±1 σ ) monazite inclusion, suggesting that ductile mid‐crustal metamorphism occurred synchronously or soon after (<10 Myr) India‐Asia collision, depending on timing. High‐resolution garnet P‐T paths from the same rock show ∼1 kbar fluctuations in P as T increases over a ∼20°C interval, consistent with a period of erosion. We report garnets from the Main Central Thrust (MCT) hanging wall that have Eocene to Miocene monazite ages, and one garnet yields paths consistent with motion along the Main Himalayan Thrust (MHT) décollement. Most high‐resolution MCT footwall P‐T paths fluctuate in P (±1 kbar) as T increases, consistent with imbrication and paths from equivalent structural assemblages in central Nepal. Like those rocks, MCT footwall (Lesser Himalayan Formation, LHF) monazite ages are Early Miocene (9.3 ± 0.6 Ma) to Pliocene (3.0 ± 0.2 Ma). The results demonstrate the consistency in timing and conditions across the MCT at locations ∼650 km apart. If the present‐day Himalayan tectonic framework has not significantly changed since the Pliocene, the LHF duplex can be considered when attributing seismic events to particular faults. The MHT is undisputedly the significant factor in accommodating Himalayan seismic activity, but MCT footwall faults may explain some shallower hypocenters, without the need for unusual MHT geometries. Plain Language Summary: The Mw 6.8 Uttarkashi earthquake occurred in the NW Indian Himalayas in 1991 and was located near a fault system termed the Main Central Thrust (MCT). Like the April 25, 2015, Mw7.8 Gorkha (Nepal) earthquake, the reported depth and fault system that triggered the earthquake is unclear. Despite being studied for decades, the geometry of the deeper portions of the Himalayan range is debated. New approaches in thermodynamic modeling allow us to obtain the highest resolution pressure‐temperature (P‐T) paths possible from garnets collected across Himalayan fault systems near the epicenters of the Uttarkashi earthquake and its aftershocks. We also date radioactive monazite in garnet‐bearing rocks beneath the MCT, which crystallized only 1–3 million years ago. Monazite in garnet collected further north are older, consistent with timing India and Asia collision ∼50 million years ago. The MCT appears to be a broad shear zone with packages of rocks moving like a deck of cards at different times. If the present‐day Himalayan framework has not significantly changed since the recent geological past, fault systems beneath the MCT may explain some of the shallower hypocenters reported for both the Gorkha and Uttarkashi earthquake and their aftershocks. Key Points: Monazite dating suggests mid‐crustal metamorphism occurred in the Tethyan Formation synchronously or soon after Indo‐Asia collision Shapes of high‐resolution garnet pressure‐temperature paths across the Main Central Thrust (MCT) in NW India indicate imbrication within the shear zone MCT footwall and duplex fault systems should be considered when attributing seismic events to particular Himalayan structures